Clonostachys rosea: Production by Submerged Culture and Bioactivity Against Sclerotinia sclerotiorum and Bemisia tabaci - Mascarin, Gabriel Moura; da Silva, Ana Vitória Reina; da Silva, Thiago Pereira; Kobori, Nilce Naomi; Morandi, Marcelo Augusto Boechat; Bettiol, Wagner (Frontiers in Microbiology, 2022)
Among the prospective biocontrol agents, the saprophytic filamentous fungus Clonostachys rosea is an excellent necrotrophic mycoparasite of numerous plant pathogenic fungi. However, its commercial development has been hampered by mass production difficulties during solid-state fermentation. Conversely, the submerged liquid fermentation shortens the cultivation time while increasing yields of fungal propagules. However, this method has been overlooked for C. rosea. In this work, we investigated the impact of liquid pre-culture inoculum on the spore production by the two-stage fermentation process using rice grains in comparison to the traditional solid-state fermentation. In parallel, we studied the submerged cultivation of C. rosea by manipulating carbon-to-nitrogen (C:N) ratio and nitrogen source, with the further optimization of spore production in a benchtop bioreactor. Additional bioassays included assessing the bioactivity of water-dispersible microgranules (that contained a submerged conidia) against the whitefly (Bemisia tabaci biotype B) and Sclerotinia sclerotiorum (causal agent of the white mold). Our results showed a maximum concentration of 1.1 × 109 conidia/g-dry-matter after 7 days of cultivation by two-stage fermentation process. The liquid fermentation yielded 1.4 × 109 submerged conidia/ml after 7 days using a medium with a 50:1 C:N ratio, and it also induced the production of microsclerotia (MS) up to 1.35 × 104/ml within 6 days with 10:1 C:N ratio; both media were supplemented with dextrose monohydrate and soybean meal. The fermentation batches carried out in a benchtop bioreactor with medium 50:1 C:N ratio and amended with soybean meal rendered a production peak on the fourth day, corresponding to 1.11 × 109 conidia/ml and 4.35 × 108 colony forming units (CFU)/ml. Following air-drying, the conidia production from air-dried microgranules of C. rosea biomass was estimated at 3.4 × 1010 conidia/g of formulated product upon re-hydration for 7 days. Both submerged conidia and MS of C. rosea inhibited 100% germination of S. sclerotiorum sclerotia by direct parasitism. The air-dried submerged conidia exhibited a suppressive activity on sclerotia (88% mycoparasitism) and early whitefly nymphs (76.2% mortality) that rendered LC50 values of 3.2 × 104 CFU/g soil and 1.5 × 107 CFU/ml, respectively. Therefore, the submerged liquid culture of C. rosea may offer a feasible and cost-effective method for its large-scale production, alleviating critical constraints to their commercial use while providing an additional tool for management of B. tabaci and S. sclerotiorum.